2015
DOI: 10.1371/journal.pone.0139186
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Heavy Drinking Does Not Affect Maturation of Basic Executive Functioning: Longitudinal Findings from the TRAILS Study

Abstract: Background and AimsExcessive alcohol use is assumed to affect maturation of cognitive functioning in adolescence. However, most existing studies that have tested this hypothesis are seriously flawed due to the use of selective groups and/or cross-sectional designs, which limits the ability to draw firm conclusions. This longitudinal study investigated whether patterns of alcohol use predicted differences in maturation of executive functioning in adolescence. Additionally, gender was tested as a possible modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 42 publications
4
25
1
4
Order By: Relevance
“…Our findings are consistent with the majority of research from neuropsychological and brain imagings that have demonstrated deficits in WM functioning in adolescents exhibiting problematic patterns of alcohol use (Squeglia et al , 2009; Squeglia et al , 2012; Peeters et al , 2014). In terms of findings from community samples, a longitudinal cohort study of Dutch adolescents (aged 11–19 years) found no evidence of an association between heavy drinking in adolescence and maturation of executive functioning (Boelema et al , 2015). The contrast in findings could be due to a number of possibilities.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our findings are consistent with the majority of research from neuropsychological and brain imagings that have demonstrated deficits in WM functioning in adolescents exhibiting problematic patterns of alcohol use (Squeglia et al , 2009; Squeglia et al , 2012; Peeters et al , 2014). In terms of findings from community samples, a longitudinal cohort study of Dutch adolescents (aged 11–19 years) found no evidence of an association between heavy drinking in adolescence and maturation of executive functioning (Boelema et al , 2015). The contrast in findings could be due to a number of possibilities.…”
Section: Discussionmentioning
confidence: 95%
“…For example, Boelema et al (2015) found no evidence of an association between heavy drinking in adolescence and maturation of executive functioning. The discrepancies in the literature could be due to a number of factors, including (a) sample size, (b) study design (high-risk vs community-based samples), (c) the alcohol use phenotype (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A recent 8-year-long prospective study (Boelema et al, 2015) did not find any association between executive functions and BD trajectory in young adults. However, the authors used simple reaction time scores as indices of cognitive processes (e.g., WM), which may lead to poor identification of subtle difficulties (e.g., manipulation, perseveration).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 79%
“…Interestingly, this may be related to the fact that perseverative errors or WM span variables were not recorded and that these variables seem to be more sensitive to weaknesses in the executive process of the WM. To our knowledge, to date only one study has examined the relationship between BD trajectory and WM in university students with no other risk factors and during a long period (Boelema et al, 2015). In the aforementioned study, the students were followed throughout 8 years and were subjected to four neuropsychological assessments.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Especially studies suggesting brain damage as a result of heavy drinking among adolescents (HillerSturmhöfel & Swartzwelder, 2004;Tapert, Granholm, Leedy, & Brown, 2002) triggered concerns among parents, teachers, and policy makers. Even though evidence for long-term brain damage among adolescents who drink alcohol was -and still is -disputed (Boelema et al, 2015), many Dutch parents may have started wondering whether the liberal approach toward adolescent drinking, that was prevailing until then, was detrimental to the health of their children.…”
Section: Societal Explanations For the Trendsmentioning
confidence: 99%